Effect of Local Transplantation of Mesenchymal Stem Cell/Macrophage Culture Supernatants on Oxidative Stress Markers in Wound Healing - Nima Mozaffari; Rahim Mohammadi; Nowruz Delirezh; Rahim Hobbenaghi; Vahid Mohammadi (Iranian Journal of Veterinary Surgery)
Skin wound healing is a complex biological process that involves a series of coordinated steps that ultimately restore the skin's integrity and function. Stem cell and macrophage secretions show promise in promoting this natural repair process. This study aims to explore the impact of locally transplanted mesenchymal stem cell/macrophage culture supernatants on oxidative stress markers during wound healing. Full-thickness wounds were created on rats. One group received local injections of a 1:1 mixture of MSC and macrophage culture supernatants, while the control group did not. After 21 days, researchers measured markers of oxidative stress and antioxidant enzyme activity in the wound tissue. The group receiving the culture supernatant mixture exhibited significantly lower levels of malondialdehyde (MDA) and total oxidant status (TOS). Additionally, they showed higher activity of glutathione peroxidase (GPx) and higher total antioxidant capacity (TAC). Local transplantation of the culture supernatant mixture improved wound healing by reducing oxidative stress and increasing antioxidant activity. These findings suggest this approach may be a promising cell-free therapy for wound healing.